Water Sanitation and Hygiene (WASH) and feeding patterns: Linkages with stunting among children aged 6-23 months - Akmal Novrian Syahruddin; Irmawati Irmawati; Novi Puspita Sari (AcTion: Aceh Nutrition Journal, 2023)
Stunting is still a significant public health problem in Indonesia. The interaction between the inadequacy of feeding practices and Water, Sanitation, and Hygiene (WASH) are the direct causes of stunting. The study aimed to assess the relationship between WASH and child feeding patterns with stunting among children aged 6-23 months. The study used a cross-sectional design conducted in July-August 2022 in the working area of Simbang Community Health Center, Maros Regency. Samples of 90 children aged 6-23 months were selected by simple random sampling. Data on sociodemographic, WASH and feeding patterns were collected by interview using a questionnaire. Stunting was measured by a height-for-age z-score. Data were analyzed using the Chi-square test and Logistic Regression. The results showed that the prevalence of stunting was 31,1%. Mother's age <20 years, low maternal height, sex of child, non-exclusive breastfeeding, complementary feeding started, the poor sewage management and availability of latrines related to stunting (p<0,05). Multivariate test results showed low maternal height (p=0,005; OR=21,015), sex of child (p=0,001; OR=22,332), poor sewage management (p=0,008; OR=10,992), and non-exclusive breastfeeding (p=0,002; OR=20,509) has a significant effect on stunting. In conclusion, the WASH and inadequacy of feeding practices contribute to stunting.